(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: Death by strangulation is most commonly homicidal in manner. Accidental strangulation is rare. In only a handful of the documented cases, the survival rate has been notably low. This can be attributed to several factors. Hypoxia can lead to organ damage and failure if not promptly addressed. Additionally, injuries to vital structures such as the carotid arteries, can have catastrophic consequences, including severe bleeding or stroke. Fractures in the neck area can also pose significant risks, as they may damage the spinal cord or cause other critical injuries. Taken together, these factors contribute to the lethal nature of this condition, emphasizing the importance of swift medical intervention and specialized care to improve outcomes. Case Report: A 15-year-old female was brought for a medicolegal autopsy at a tertiary care institute in southern Haryana with a history of road traffic accident. As per the history, the deceased was wearing a long dupatta (scarf) and was a pillion rider of a two-wheeler. Her dupatta got entrapped into the rear wheel of bike. The patient presented with chief complaints of difficulty in speech and pain in the neck region. She was managed conservatively for an initial two days but suddenly developed respiratory distress on the third day and succumbed to death on day four after sustaining the initial injury. Conclusion: As such, healthcare providers must remain attentive to the potential signs and symptoms of Long Scarf Syndrome, especially in cases of suspected strangulation. Furthermore, this case report emphasizes the importance of thorough medical evaluation and multidisciplinary care in optimizing patient outcomes. Collaborative efforts between emergency physicians, trauma specialists, and other healthcare professionals are essential in delivering timely and effective interventions to mitigate the risks associated with Long Scarf Syndrome.